1976
DOI: 10.1109/tcom.1976.1093228
|View full text |Cite
|
Sign up to set email alerts
|

Image Activity Characteristics in Broadcast Television

Abstract: Real-time processing of video waveforms has been implemented for the purpose of analyzing image dynamics. A digital preprocessor yields data sets that describe the difference between selected fields of an input video signal in both the spatial and temporal domains. Further reduction and analysis of the acquired data can provide several measures of image activity such as the frame-to-frame correlation, the framedifference signal (FDS), and statistics of scene lengths. The results of a series of measurements of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

1977
1977
2002
2002

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 0 publications
0
6
0
Order By: Relevance
“…This finding is consistent with the applicability of the models of Eqs. 6 and 7 in earlier studies of spatial and temporal statistics [2,5,7,8,9].…”
Section: Figure 2 Near Herementioning
confidence: 87%
See 1 more Smart Citation
“…This finding is consistent with the applicability of the models of Eqs. 6 and 7 in earlier studies of spatial and temporal statistics [2,5,7,8,9].…”
Section: Figure 2 Near Herementioning
confidence: 87%
“…An exponential autocorrelation function has been shown to be a good model for temporal frame to frame correlations of image sequences [e.g., 5,6,7,8], and for spatial correlations within each frame [e.g., 2, 3, 9].…”
Section: Introductionmentioning
confidence: 99%
“…In order to do so, suitable probability distribution needs to be found first. Studies reported in [22] and [7], involving statistical measurements of shot lengths for a large number of motion pictures, have shown that the distribution of shot lengths for all the films considered matches the Poisson function well [21]. Therefore, we adopt the Poisson function as the base for computing the cumulative probability .…”
Section: A Priori Probability Functionmentioning
confidence: 99%
“…Since the second item requires that the function converges toward the value 0.5, cumulative probability values need to be halved in order to ensure proper convergence, that is (21) The parameter of the Poisson distribution in (21) represents the average shot length of a video sequence, is the frame counter, which is reset each time a shot boundary is detected, and is the current shot length at the frame . The Poisson function was obtained in [7] and [22] as most suitable for motion pictures. However, we assume that the conclusions on shot-length distributions made by Salt and Coll can be extended further to all other types of video programs.…”
Section: A Priori Probability Functionmentioning
confidence: 99%
“…26 Further statistical analysis can also yield valuable clues for film genre detection and style characterization. 19,27,28 For our application, we express the duration dur s of a shot s in minutes; i.e., dur s ϭ Number of frames in s 60•frame rate ͑fps͒ . ͑3͒…”
Section: Shot Duration and Pacingmentioning
confidence: 99%